BIBLIOMETRIC ANALYSIS OF BIG DATA RESEARCH IN FINANCE - Farhan Afie Ar-Raisi; Eklamsia Sakti; Alexander Anggono; Tarjo Tarjo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Big data consists of structured and unstructured data. In the finance area, the data is extensively applied for business development. Consequently, researches on this area are growth in a fast pace. Hence, this study is intended to portray trend of several previous studies concerning of big data in the financial sector. Data sources refer to articles searched in the Science Direct, Emerald Insight and Google Scholar. Based on the purposive sampling method, it is acquired 61 papers. Findings of this study indicate that those papers mostly were published by the Science Direct. The research method mostly applied in those studies was a qualitative approach. Most of the papers in this area were published during the 2017 and China was a country that was frequently used as an object of study. The University of Minho was an institution that actively doing research in this area. The Procedia Computer Science was the most active publishing journal, and the decision making was an area that was frequently researched.